Akibat Hukum Pemutusan Internet oleh Pemerintah Saat Demonstrasi dan Kerusuhan - I Gede Nyoman Aditya Riana Triputra; I Nyoman Putu Budiartha; Luh Putu Suryani (Warmadewa Press, 2022)
Internet is an important tool in aspects of human life today. However, what if the internet network in one area or more within a country is restricted or even cut off, such as the people of Papua and West Papua who are affected by internet disconnection during demonstrations, resulting in riots between civil society and the state apparatus. The purpose of this study is to find out the legal sanctions against internet disconnectors during demonstrations and riots and the judge's consideration of internet disconnectors during demonstrations and riots (Study of Decision No. 230/5.TF/2019/PTUN-JKT)? This research uses normative legal research type. Sources of data come from primary, secondary and tertiary, collected by literature study. The data were analyzed with the technique of understanding the laws of deductive and inductive logic. The results of the study show that legal sanctions that can be imposed on the government are fully decided by the State Administrative Officer in the State Administrative Court. Then, in terms of the judge's consideration in deciding the case, it is based on the provisions of Article 110 jo. Article 112 of Law Number 5 of 1986 concerning the State Administrative Court.